Inter-Generational Retreat Program as a Form of Comprehensive Christian Religious Education - Tarumingi, Denny Adri; Paendong, Gloria Kurnia; Lontoh, Andheralvi Isaiah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This research aims to analyze and develop the concept of intergenerational retreat programs as a form of comprehensive Christian Religious Education (PAK), as well as explain its contribution to the formation of spirituality and intergenerational relations in church life. This research uses a qualitative method with a library research approach that is a conceptual paper. Data was obtained from various sources of scientific literature in the form of books, national and international journal articles, and other academic references published in the 2014–2024 range. The literature was obtained through searches on Google Scholar databases, ResearchGate, Directory of Open Access Journals (DOAJ), and BASE, with a focus on Christian religious education practices and intergenerational retreats in the context of churches in Indonesia. Data analysis was carried out using content analysis techniques through the stages of data reduction, theme categorization, and conceptual synthesis. The results of the study show that intergenerational retreats are a comprehensive model of Christian religious education because they integrate cognitive, affective, and psychomotor aspects in one faith learning experience. In addition, this model is able to strengthen spirituality, build intergenerational relationships, and overcome the tendency of age segregation in church service. Thus, intergenerational retreats can be a strategic alternative for churches in Indonesia in developing inclusive, participatory, and sustainable Christian religious education.